Suppress Students’ Bullying Through Collaborative Guidance And Counseling Services With Democratic Parenting - Anjasari, Titi; Raharjo, Arif Budi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to find out: 1) The effect of guidance and counseling services on bullying behavior, 2) The effect of democratic parenting levels on bullying behavior, 3) The contribution of each variable of counseling guidance services and democratic parenting levels on bullying behavior, 4) Contributions together of counseling guidance services and democratic parenting levels on bullying behavior. This research was conducted at SMP Muhammadiyah 1 Mlati, the sample in this study consisted of 77 respondents. This research is quantitative research which means that all information or data obtained is realized in the form of numbers, starting from data collection and results. Data analysis using multiple regression analysis test. The results of this study show: 1) There is an influence between counseling guidance services on bullying behavior. 2) There is an influence between the level of democratic parenting and bullying behavior. 3) The variable effective contribution of counseling guidance services to bullying behavior was 5.1%, while the variable effective contribution of democratic parenting to bullying behavior was 1.5%. 4) Effective contribution together of counseling guidance services and democratic parenting levels to bullying behavior by 7.9%. The implication of this study is that in reducing student bullying behavior is carried out by improving teacher counseling guidance services in schools and democratic parenting at home.